Exploring the Hydroelectric Potential of Thulagi Glacial Lake for Risk Reduction and Sustainable Energy in the Himalayas - Ghimire, Sudan; Ghimire, Motilal (Nepal Journal of Environmental Science, 2025)
Glacial Lake Outburst Floods (GLOFs) represent one of the most devastating natural hazards in the Himalayas, with their unpredictable nature leading to significant infrastructure and economic damage in Nepal. While this resource has the potential to benefit society, it poses a risk to communities located downstream. This research primarily aims to investigate the hydroelectric potential of the Thulagi glacial lake in Manang district of Nepal, focusing on risk reduction and sustainable energy solutions in the Nepali Himalayas. The study is confined to the context of Nepal and serves as a preliminary investigation rather than a detailed technical evaluation. Data was gathered using a conductivity meter, revealing a maximum discharge rate of 6155.22 l/s on 23 August 2018. The lake’s area, glacier, and volume were assessed through satellite imagery, which indicated significant expansion of the lake and substantial retreat of the Thulagi glacier from 2005. Despite the glacier’s rapid recession, it is estimated that it will continue to supply water to the Thulagi Lake for over a thousand years. The lake contains approximately 35.7 million cubic meters of water, with an annual discharge of about 93.4 million cubic meters. Even with the minimal required gross head and turbine efficiency for micro-hydropower, the lake’s maximum discharge rate could generate 102 kW of energy. By harnessing the lake’s water for energy production, the risks associated with the lake can be transformed into economic benefits.